PENGGUNAAN BAHAN PEMUCAT PADA PRODUKSI KACANG GARING (The Use of Bleach in Crispy Peanut Production) - Setianingsih, Nanik Indah; Christianto, Herry Yuli; Nilawati, Nilawati (Jurnal Hasil Penelitian Industri, 2014)
Some of crispy peanut industry used alum as additive in order to make thecolor of peanut looks white and clean. Using alum in food production is not recommended,because alum is unlisted as additive food and also has negatif effect for health. The aim ofthis research was to find additive to replace alum in crispy peanut production, effective inbleaching and donât have negatif effect for health. This research used completly randomfactorial design with kind of bleach and time of dyeing factor. The result of variantanalysis of lightness level parameter show that 87,5% of treatment resulted lightness levelvalue different with control significantly. Most of optimal lightness level value be obtainedin using 1% of bleach both of calcium sulfat and calcium oxide. Use of calsium sulfatresulted higher of lightness level value than calsium oxide. The result of organoleptic testshow that panelist liked taste, texture and color of crispy peanut commonly. Treatmentwith time of dyeing and kind of bleach 1% concentration did not affecting the difference inorganoleptic valuation significantly. The result analysis base of quality requirements,crispy peanut with time of dyeing and kind of bleach 1% concentration treatment meet thedetermined standard.